Metode Storytelling sebagai upaya mengembangkan Percaya Diri pada anak Pasca Gempa di Cianjur - Mulyana, Indah (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2023)
The purpose of this study was to develop self-confidence skills through storytelling methods or telling stories to children aged 5-6 years after the earthquake in Cianjur, West Java. The design used includes a qualitative research approach with descriptive analysis methods. Data collection techniques use interviews, observation, and documentation. This research was conducted in Sarampad village, Cibulak village, Cigenang District. Cianjur Regency, West Java province. In this study, it was found that the storytelling method can be used as an effort to develop children's confidence after the earthquake in Cianjur. With observations made during the implementation of this study with stages of planning, implementation and evaluation showed a good and enthusiastic response of children participating in activities. With this, researchers concluded that the Storytelling method was effectively used to develop children's self-confidence after the earthquake in Cianjur, West Java.